A Literature Review on Vocational Interest Measurements Using Bibliometric Analysis - Bagaskara, Rafli Sodiq; Assa, Nadim Alfan (Buletin Psikologi, 2025)
Vocational interest assessments play an important role in supporting high school students in identifying appropriate career paths, particularly for those planning to pursue tertiary education. Nevertheless, a comprehensive evaluation of the literature is essential to assess the relevance, gaps, and current state of vocational interest measurement. Therefore, this study aimed to analyze global publication trends and research related to vocational interest assessment. Using a bibliometric approach, 232 articles were retrieved from the Dimensions AI database, covering the period from 1924 to 2024. The Journal of Vocational Behavior emerged as the most prominent journal in this field, while James B. Round from the University of Illinois, Urbana-Champaign was identified as the most influential author. Between 2014 and 2024, 62 relevant publications were recorded, including six from Indonesia. This study offered insights into publication growth, author affiliations, and key themes while identifying underdeveloped areas requiring further exploration in the measurement of vocational interest.